contestada

Given: F = {(0, 1), (2, 4), (4, 6), (6, 8)} and G = {(2, 5), (4, 7), (5, 8), (6, 9), (7, 5)}

(F + G) (2) =

Given: F = {(0, 1), (2, 4), (4, 6), (6, 8)} and G = {(2, 5), (4, 7), (5, 8), (6, 9), (7, 5)}

(F - G) (6) =


Given: F = {(0, 1), (2, 4), (4, 6), (6, 8)} and G = {(2, 5), (4, 7), (5, 8), (6, 9), (7, 5)}

(F  G) (2) =



Respuesta :

(f + g) (2) = f (2) + g (2) = 4 + 5 = 9

(f - g) (6) = f (6) - g (6) = (input the chosen values)

(fg) = f*g = (input the chosen values)

If this helps give a brainliest ;)


Answer with Step-by-step explanation:

F = {(0, 1), (2, 4), (4, 6), (6, 8)}  

G = {(2, 5), (4, 7), (5, 8), (6, 9), (7, 5)}

(F+G)(2)=F(2)+G(2)

            = 4+5

            = 9

F = {(0, 1), (2, 4), (4, 6), (6, 8)}  

G = {(2, 5), (4, 7), (5, 8), (6, 9), (7, 5)}

(F - G) (6) =F(6)-G(6)

               =8-9

               =-1

F = {(0, 1), (2, 4), (4, 6), (6, 8)}

G = {(2, 5), (4, 7), (5, 8), (6, 9), (7, 5)}

(F.G) (2) =F(2).G(2)

             = 4×5

            = 20

ACCESS MORE